Reframing English Language Teaching: Indonesian Teachers’ Views on World Englishes and the Role of Linguistic Diversity in the Classroom - Sri Nurhayati; Slamet Setiawan; Him'mawan Adi Nugroho; Muhammad Safdar Bhatti (English Department, Universitas Negeri Surabaya, 2025)
In today’s multilingual world, English is broadly used not only in standardized forms of British or American English but also diverse localized varieties around the world. This condition requires the non-native English speaker to be aware of the World Englishes. However, teachers’ knowledge and attitudes play a key role in the effective integration of WE in classrooms. This study employed a qualitative descriptive design to explore the English teachers’ knowledge of WE and its implications for future teaching practices. Data were collected from a close and open-ended questionnaire distributed to 73 teachers across secondary and Islamic education institutions. Descriptive statistics were used in analyzing data about the teachers’ awareness of WE, teaching preferences, and perceived challenges. The results show that 76.6 percent of participants had prior knowledge of WE, while 89.6% supported its inclusion in classroom instruction. 43 percent preferred British English, 30 percent American English and 26 percent expressed flexible or mixed approaches. Teachers highlighted the importance of WE to global perspective, communication skills, and respect for linguistic diversity as potential benefits. However, challenges such as limited exposure and lack of institutional support were noted. Viewed through World Englishes and English as a Lingua Franca (ELF) theory, these findings underscore the pedagogical need to move beyond native-speaker norms toward more inclusive and context-sensitive ELT practices in Indonesia.